2021
DOI: 10.1111/jce.14951
|View full text |Cite
|
Sign up to set email alerts
|

First experience of POLARx™ versus Arctic Front Advance™: An early technology comparison

Abstract: Introduction Cryoballoon ablation is an established technique to achieve pulmonary vein isolation in patients with atrial fibrillation (AF). Recently, a new manufacturer of cryoballoon achieved regulatory CE marking (POLARx™; Boston Scientific). We describe our early experience of using this new market entrant of the technology and describe procedural aspects in comparison to the incumbent Medtronic Arctic Front Advance™. Methods We assessed the first 40 AF ablations performed with the POLARx catheter at the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 12 publications
13
58
0
Order By: Relevance
“…Recently, a new CB technology (POLARx™; Boston Scientific) has come onto the market. Preliminary data [3][4][5] have shown that its acute safety and efficacy are similar to those of the Arctic Front Advance™ CB. However, the behavior of the biophysical parameters associated with cooling seems different between the two systems [3][4][5].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, a new CB technology (POLARx™; Boston Scientific) has come onto the market. Preliminary data [3][4][5] have shown that its acute safety and efficacy are similar to those of the Arctic Front Advance™ CB. However, the behavior of the biophysical parameters associated with cooling seems different between the two systems [3][4][5].…”
Section: Introductionmentioning
confidence: 97%
“…Preliminary data [3][4][5] have shown that its acute safety and efficacy are similar to those of the Arctic Front Advance™ CB. However, the behavior of the biophysical parameters associated with cooling seems different between the two systems [3][4][5]. The aim of this study was to evaluate procedural and biophysical parameters resulting in acute PV isolation when using this new CB.…”
Section: Introductionmentioning
confidence: 97%
“…One of the unique features of this cryoballoon is that it maintains a uniform pressure and size during inflation and cryoablation. Several centers have published their initial clinical experience with this POLARx cryoablation system and have compared it with the fourth‐generation Arctic Front Advance Pro (AFA‐Pro) cryoballoon (Medtronic) 9–12 . Most of these studies are limited by their small sample size, observational design, and single‐center design.…”
Section: Introductionmentioning
confidence: 99%
“…One comparative study comparing Arctic Advance and POLARx demonstrated shorter TTI in the POLARx group (44.8 s vs 39 s) [ 19 ]. Another study by Creta et al suggested increased ablation time in the right-sided PV, contradicting the assumption the more maneuverable POLARSHEATH would ease access to these veins [ 20 ▪ ]. This early clinical data also shows some increased procedural time, LA dwell time, and increased fluoroscopy when using the POLARx system, which could be attributed to operators adapted to the use of new devices.…”
Section: The Boston Scientific Polarx Vs Medtronic Arctic Front Advancementioning
confidence: 99%